1997
DOI: 10.1159/000262208
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Variations in Trisyllabic Sequences of Thai Tones

Abstract: It is well known that tones assimilate in much the same way as consonants and vowels do. In tonal assimilation, the height and shape of a given tone is altered by adjacent tones. Earlier studies on tonal assimilation in Thai have used two-tone sequences with an intervening obstruent between the two tones of interest. In the present study, three-tone sequences were used with continuously voiced syllables throughout the utterance. Assimilatory effects were expected to be greater between F₀ contours of two succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 7 publications
(9 reference statements)
1
28
0
Order By: Relevance
“…Second, the current version of PENTAtrainer2 simulates only F 0 variations due to the normal target approximation process. It has not incorporated algorithms for simulating additional articulatory mechanisms, including, in particular, anticipatory raising (Gandour et al, 1994;Potisuk et al, 1997;Xu, 1999), post-low bouncing (Chen and Xu, 2006), consonantal perturbation (Silverman, 1986) and vowel intrinsic pitch (Whalen and Levitt, 1995). Of these, post-low bouncing has already been simulated in a separate study by adding an extra component added to qTA (Prom-on et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the current version of PENTAtrainer2 simulates only F 0 variations due to the normal target approximation process. It has not incorporated algorithms for simulating additional articulatory mechanisms, including, in particular, anticipatory raising (Gandour et al, 1994;Potisuk et al, 1997;Xu, 1999), post-low bouncing (Chen and Xu, 2006), consonantal perturbation (Silverman, 1986) and vowel intrinsic pitch (Whalen and Levitt, 1995). Of these, post-low bouncing has already been simulated in a separate study by adding an extra component added to qTA (Prom-on et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, particularly in short-short vowel combinations, when H tone was followed by tones that approach a relatively low F 0 , such as M, L or R, the synthesized contours are lower than the original. Since the same pitch targets can simulate H tone in other cases, this error could be attributed to the wellestablished phenomenon of anticipatory raising (Gandour et al, 1994;Potisuk et al, 1997). Also, consistent mismatches in the H-H sequence in both long-long and short-short vowel combinations, but not in other H-tone related cases, suggest that speakers may have slightly changed the pitch target for a second H tone by increasing either slope or strength.…”
Section: Graphical Comparisonmentioning
confidence: 99%
“…In each utterance, the first and third syllables were stressed, the latter being the reduplicated adverbial itself. For each reduplicative adverb, the tonal environment is constant, thus controlling for effects of tonal coarticulation [Gandour et al, 1994;Potisuk et al, 1997]. All five target words began with a sonorant.…”
Section: Methodsmentioning
confidence: 99%
“…The 125 sample words of 3 tone sequences were combinations of syllables in the first set: {/niaN/, /nòoN/, /nŴaN/, /nÓON/, /nǑON/}, together with syllable in the second set: {/yOO/, /yÈE/, /wâa/, /lÓO/, /lǐi/} and the third set: {/naaN/, /lÒOn/, /lâam/, /náam/, /lǎan/} (16) . All sample words begin with nasal, lateral or semivowel consonants, and the vowels for all 3 syllables were long vowels.…”
Section: Speech Materialsmentioning
confidence: 99%
“…In Thai tones, Potisuk et al (16) showed that coarticulation effect restricted to continuous tones. In this experiment, we assume the interaction between adjacent tones in continuous speech should be the same patterns.…”
Section: Suprasegmental F 0 Contour Generationmentioning
confidence: 99%